A prospective comparison of the performance and survival of two different tunnelled haemodialysis catheters: SplitCath® versus DuraMax®. Issue 4 (July 2017) - McGarry, James G.; Given, Mark F.; Whelan, Adrian; O'Kelly, Patrick; Connaughton, Derval; McGrath, Frank P.; Keeling, Aoife N.; Conlon, Peter J.; Lee, Michael J.
Background: Despite their well-recognised shortcomings, haemodialysis catheters (HDCs) remain an important form of haemodialysis access for many patients. There are several HDCs commercially available, each differing considerably in design, which is known to significantly influence performance and survival. We sought to determine which of two tunnelled HDCs, DuraMax ® (Angiodynamics, NY, USA) or SplitCath ® (MedComp, PA, USA) delivers the best performance, safety and reliability for dialysis patients. Methods: Eighty-six patients were prospectively randomised to receive either DuraMax ® (DM) or SplitCath ® (SC). Outcomes included: (i) mean flow rates (mL/min) averaged over the first 10 weeks of dialysis, and urea reduction ratio (URR); and (ii) long-term catheter survival with appraisal of any events leading to catheter dysfunction and early removal. Results: Median flow rates (interquartile range) in the DM and SC groups were 321 (309-343) and 309 (294-322) mL/min, respectively (p = 0.002). URR values for the DM and SC groups were 71 (65-76) and 74 (70-78), respectively, (p = 0.094). There was no significant difference in long-term survival or frequency of incidents that required early HDC removal (9/43 in the DM group, 5/43 patients SC). A slightly higher incidence of HDC dislodgement was noted in the DM group, although this study was not statistically powered to determine its significance. Conclusions: We conclude that DM yields slightly higher flow rates in the first 10 weeks of dialysis, and a similar low incidence of complications and long-term survival for both DM and SC HDCs.